Manic episode, aggressive behavior and poor insight are significantly associated with involuntary admission in patients with bipolar disorders - Luo, Chenyuli; Chen, Hui; Zhong, Shaoling; Guo, Huijuan; Li, Qiguang; Cai, Weixiong; Girolamo, Giovanni de; Zhou, Jiansong; Wang, Xiaoping (PeerJ, 2019)
Objective(s) Serious mental illnesses, such as bipolar disorders and schizophrenia, are closely associated with involuntary admission. Many studies have focused on involuntary admission in people with schizophrenia, but little is known about the factors associated with involuntary admission in Chinese patients with bipolar disorders. This study aimed to investigate socio-demographic and clinical factors associated with involuntary admission in Chinese patients with bipolar disorders. Methods In this multi-center cross-sectional survey in China, a total of 155 newly admitted patients with bipolar disorders were consecutively recruited from 16 psychiatric institutions from 15 March to 14 April, 2013. Patients’ socio-demographic and clinical data were collected from their medical records. The Modified Overt Aggression Scale and the Insight and Treatment Attitudes Questionnaire were used to measure patients’ level of aggression and insight of current psychiatric illness. Results The prevalence of involuntary admission was 52% in this sample of Chinese inpatients with bipolar disorders. In multiple logistic regression, a high level of aggression (odds ratio (OR) = 2.48), diagnosis of manic episode (OR = 3.65), poor insight (OR = 7.52), and a low level of education (OR = 3.13) were significantly associated with involuntary admission. Conclusion Manic episode, aggressive behavior, and poor insight were the significant contributing factors to involuntary admission in Chinese patients with bipolar disorders.
Keywords: Involuntary admission; Bipolar disorder; Aggressive behavior